YAP Controls Endothelial Activation and Vascular Inflammation Through TRAF6. Issue 1 (22nd June 2018) - Lv, Yang; Kim, Kyungho; Sheng, Yue; Cho, Jaehyung; Qian, Zhijian; Zhao, You-Yang; Hu, Gang; Pan, Duojia; Malik, Asrar B.; Hu, Guochang
Abstract : Rationale: : Microvascular inflammation and endothelial dysfunction secondary to unchecked activation of endothelium play a critical role in the pathophysiology of sepsis and organ failure. The intrinsic signaling mechanisms responsible for dampening excessive activation of endothelial cells are not completely understood. Objective: : To determine the central role of YAP (Yes-associated protein), the major transcriptional coactivator of the Hippo pathway, in modulating the strength and magnitude of endothelial activation and vascular inflammation. Methods and Results: : Endothelial-specific YAP knockout mice showed increased basal expression of E-selectin and ICAM (intercellular adhesion molecule)-1 in endothelial cells, a greater number of adherent neutrophils in postcapillary venules and increased neutrophil counts in bronchoalveolar lavage fluid. Lipopolysaccharide challenge of these mice augmented NF-κB (nuclear factor-κB) activation, expression of endothelial adhesion proteins, neutrophil and monocyte adhesion to cremaster muscle venules, transendothelial neutrophil migration, and lung inflammatory injury. Deletion of YAP in endothelial cells also markedly augmented the inflammatory response and cardiovascular dysfunction in a polymicrobial sepsis model induced by cecal ligation and puncture. YAP functioned by interacting with the E3 ubiquitin-protein ligase TLR (Toll-like receptor) signaling adaptor TRAF6 (tumor necrosis factor receptor-associated factor 6) to ubiquitinate TRAF6, and thus promoted TRAF6 degradation and modification resulting in inhibition of NF-κB activation. TRAF6 depletion in endothelial cells rescued the augmented inflammatory phenotype in mice with endothelial cell–specific deletion of YAP. Conclusions: : YAP modulates the activation of endothelial cells and suppresses vascular inflammation through preventing TRAF6-mediated NF-κB activation and is hence essential for limiting the severity of sepsis-induced inflammation and organ failure. Abstract : Supplemental Digital Content is available in the text.